Ground‐Dwelling Spider Community Responses to Forest Management in a Mediterranean Oak Forest - Claire Ménival; Mathieu Santonja; Christophe Mazzia; Valentin Spataro; Lenka Brousset; Daniel Pavon; Sylvie Dupouyet; Yoann Le Bagousse‐Pinguet; Raphaël Gros (Ecology and Evolution, 2025)
ABSTRACT Timber production is one of the most important ecosystem services provided by hardwood forests, but clear‐cutting causes severe soil disturbance. There is a current need to develop alternative forest management practices to clear‐cutting in order to simultaneously promote timber production, preserve biodiversity and enhance forest health and economic value. Here, we experimentally manipulated a Quercus pubescens forest to evaluate the effects of a thinning gradient (i.e., partial tree removal) ranging from 25% to 75% basal area reduction and a logging residue retention (i.e., slash management) on ground‐dwelling spider abundance and species richness. These two alternative management practices were compared with clear‐cutting (100% basal area reduction) and logging residue exportation methods. In each treatment, we recorded soil temperature and moisture, understorey vegetation cover, richness and functional traits and mesologic factors describing habitat characteristics. We found clear‐cutting had a stronger effect than thinning on the microclimatic conditions, i.e., higher temperatures, drier soils and reduced forest buffering capacity. The 25% thinning intensity was sufficient to drastically reduce both spider abundance and richness, but we did not find a more significant reduction when more intensive cutting was applied. This result suggests a threshold effect in the response of spiders to cutting. Significant changes in the functional diversity of understory plant communities in response to basal area were observed, along with strong effects on spider communities. Unexpectedly, slash retention appeared to have little or no effect on the forest microclimate, spider abundance and species richness. This work is intended for forest managers and policymakers and aims to contribute to the development of relevant practices that address current environmental and economic challenges. While our findings provide valuable insights into understudied forest management practices in Mediterranean climates, additional research is required, particularly through multi‐seasonal and long‐term spider sampling.